1997
DOI: 10.1557/jmr.1997.0397
|View full text |Cite
|
Sign up to set email alerts
|

Surface nucleation, domain growth mechanisms, and factors dominating superconducting properties in seeded melt grown YBa2Cu3Ox

Abstract: Using a seeded melt growth (SMG) method, we have produced single-domain YBa2Cu3Ox with high levitation forces and trapped magnetic fields. A threshold temperature TL has been found above which extraneous nucleation does not occur. Surface nucleation has been suppressed when the top sample surface is coated with low melting compounds. The planar growth rates along the a- and c-axes have been found to be comparable within the undercooling range used in this study, and agree well with the current model. Major fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…For sintered YBCO bulk, the levitation force is very small, is proportional to the thickness and is saturated, while the sample's thickness is larger than 5 mm [22]. But, for well-textured YBCO bulk superconductors, the levitation force increases linearly with the increase of thickness and is not saturated up to 12 mm [23]. The linear dependence of levitation force on the thickness of YBCO bulk is in good agreement with the theoretical formula [31]…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…For sintered YBCO bulk, the levitation force is very small, is proportional to the thickness and is saturated, while the sample's thickness is larger than 5 mm [22]. But, for well-textured YBCO bulk superconductors, the levitation force increases linearly with the increase of thickness and is not saturated up to 12 mm [23]. The linear dependence of levitation force on the thickness of YBCO bulk is in good agreement with the theoretical formula [31]…”
Section: Introductionsupporting
confidence: 77%
“…In addition, the levitation force of the YBCO bulk is also related to many parameters, such as the thickness of the sample [22,23], the magnetic field distribution [24][25][26], grain orientation [27][28][29], temperature and the gap between a superconductor and a magnet [30], etc. For sintered YBCO bulk, the levitation force is very small, is proportional to the thickness and is saturated, while the sample's thickness is larger than 5 mm [22].…”
Section: Introductionmentioning
confidence: 99%
“…For a normal conductor such as copper, the surface resistance is of the order of 0.01 at a frequency of 2 GHz [1,2]. The surface resistance is many orders of magnitude below this at the same frequency range in well textured YBCO, making this HTS material an attractive candidate for rf components [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. To achieve low surface resistance, the current approaches in processing HTSs are thin-film technologies, which can produce epitaxially grown films with low surface resistance [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Shi et al found that the levitation force of single domain YBCO bulk superconductor fabricated by the TSMG method decreases linearly with the decreasing thickness, which may be attributed to the small size of the magnet employed in the study. [21] Kütük et al found that the levitation force density of YBCO bulks fabricated using the flame-quench-melt-growth method improves with the decrease of sample thickness, which is associated with a significant amount of precipitated phase at the bottom of the sample. [22] In Ref.…”
Section: Introductionmentioning
confidence: 99%